Analyzing the Impact of Attractions, Accessibility, and Facilities on Customer Value in Tourism Destinations - Zebua, Mardalena; Narimawati, Umi; Juju, Undang (Almana : Jurnal Manajemen dan Bisnis, 2025)
Abstract: Tourism is a strategic sector that stimulates economic growth and community welfare, yet in many destinations the perceived value by tourists remains moderate due to weaknesses in attractions, accessibility, and facilities. This study aims to analyze the influence of these three factors on customer value in tourist destinations. The research used a quantitative approach with 400 respondents selected through proportional cluster random sampling in coastal areas. Data were analyzed using Structural Equation Modeling (SEM) with LISREL to test the causal relationships and measurement model validity. The results indicate that attractions, accessibility, and facilities significantly and positively affect customer value, explaining 68.9% of its variance, with attractions having the strongest effect (36.7%), followed by accessibility (31.5%) and facilities (23.2%). Descriptive findings show that these variables are perceived as â€œfairly goodâ€ to â€œgood,â€ with comfort contributing most to customer value, while efficiency remains low. The study concludes that strengthening sustainable attractions, improving digital and physical accessibility, and enhancing facility completeness and quality are essential strategies to elevate customer value and competitiveness of tourist destinations. These findings provide practical insights for managers and policymakers to improve service quality and tourist satisfaction systematically.